Neoadjuvant systemic treatment for breast cancer in Italy: The Italian Society of Surgical Oncology (SICO) Breast Oncoteam survey. Issue 8 (August 2018) - Vicini, E.; Invento, A.; Cuoghi, M.; Bafile, A.; Battaglia, C.; Biglia, N.; Busani, M.; Bussone, R.; Cianchetti, E.; Caruso, F.; Cucchi, M.C.; Dessena, M.; et al.
Abstract: The Italian Society of Surgical Oncology (SICO) Breast Oncoteam developed a survey to explore the state of the art of neoadjuvant treatment for breast cancer in Italy, specifically focusing on cases treated during the two-year period 2014–2015. A questionnaire was sent to Italian Breast Units with a minimum of 150 new breast cancer cases treated/year according to the Senonetwork directory and to the SICO Breast Oncoteam Breast Unit network. A total of 23/107 Breast Units submitted the survey, reporting a total amount of 20156 cases of breast carcinoma (17241 invasive, 2915 in situ) treated in the biennium, corresponding approximately to 20% of newly diagnosed breast cancers in Italy. In the United States, medical treatment before surgery for breast cancer is indicated in about 22.7% of newly diagnosed cases according to the National Cancer Database, while a German study reported approximately 20% of cases treated with neoadjuvant therapy. In our survey, a total of 1673/17241 cases (9.7%) were treated with neoadjuvant therapy, ranging from 2.9% to 23.6% according to different centres, showing heterogeneity in neoadjuvant treatment indications, even in multidisciplinary breast units. Better resources should be engaged to achieve a standardised quality indicator for neoadjuvant treatment, and this indicator could be included among the European Society of Breast Cancer Specialists (EUSOMA) quality indicators. In the near future, we plan to develop a second survey to better test improvements in the employment of neoadjuvant therapy after the expiry of the 2016 European Parliament deadline and after the 2017 St. Gallen Conference recommendations.